Role of Satoyama Forest towards Sustainability: Contributing to Carbon Stock in Japan (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
This study investigated the potentials of Satoyama forests to contribute in increasing carbon stock by inclusion of controlled biomass harvesting in the forms of thinning and pruning under a planned forest management intervention. A Satoyama forest named Oaota in Kashiwa, Chiba, Japan was selected for the study. We calculated present carbon stock of the forest by using sample data from four quadratic plots (two in each site) from which we measured the diameter and height of trees including the diameter and length of branches. Five conical shaped leaf traps were used to measure the amount of leaf biomass production in a year. Soil organic carbon was analyzed by NC analyzer for 0-30 cm depth of soil. The study revealed that the Oaota forest contributed to carbon capture in the forms of 158.7 tC/ha (80.95 tC/ha for soil, 76.19 tC/ha for wood and 1.63 tC/ha/y for leaves). Soil carbon accumulation was not considered in this study. The results indicated that by harvesting planned amount of biomass to consume as a zero-emission renewable fuel alternative to replace high carbon emission fuels may help reduction in carbon releases and enhances the carbon capture performace as well as revitalization of Satoyama forests.
Keywords: Satoyama; sustainablity; carbon stock; conservation